2003
DOI: 10.1016/s1062-1458(03)00323-4
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of mitral valve regurgitation after mitral valve repair in degenerative valve disease

Abstract: Background-Durability assessment of mitral valve repair for degenerative valve incompetence is actually limited to reoperation as the primary indicator, with valve-related risk factors for late death as a secondary indicator. We assessed serial echocardiographic follow-up of valve function as an indicator of the durability of mitral valve repair. Methods and Results-In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…Particularly when a prosthetic ring is used, a concomitant annuloplasty, besides remodeling the annulus and forcing leaflet coaptation, stabilizes the repair over time preventing annular redilatation and reducing the risk of late failure. The benefits of annuloplasty in valve repair have been confirmed by several authors [1][2][3][4] who found that the absence of annuloplasty was one of the most important risk factor for late failure of the repair. As far as the EE technique is concerned, in patients with degenerative MR, the long-term results of this procedure are excellent whenever an annuloplasty is concomitantly used.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Particularly when a prosthetic ring is used, a concomitant annuloplasty, besides remodeling the annulus and forcing leaflet coaptation, stabilizes the repair over time preventing annular redilatation and reducing the risk of late failure. The benefits of annuloplasty in valve repair have been confirmed by several authors [1][2][3][4] who found that the absence of annuloplasty was one of the most important risk factor for late failure of the repair. As far as the EE technique is concerned, in patients with degenerative MR, the long-term results of this procedure are excellent whenever an annuloplasty is concomitantly used.…”
Section: Discussionmentioning
confidence: 83%
“…Particularly when a prosthetic ring is used, repair durability is enhanced by increased leaflet coaptation and prevention of further dilatation of the mitral annulus. [1][2][3][4] After the introduction of the MitraClip system, however, MR has been treated in many patients by applying a percutaneous ringless edge-to-edge (EE) procedure. Defining the long-term results of the surgical EE repair performed without annuloplasty may help to foresee, at least partially, the possible late results of this percutaneous technique.…”
mentioning
confidence: 99%
“…In our clinical practice, we perform mitral repair in each individual coronary case presenting with severe (3-4) MR. As an accepted guideline recommendation, general practice should be to correct severe MR during coronary artery bypass graft surgery; however, MR recurrence may occur despite successful revascularization and mitral repair (24). Ischemic MR carries a definite risk for higher mortality in the presence of poor ventricular function (7). This can be associated with ongoing ischemic myocardial dysfunction that leads to progressive annular dilatation and lateral displacement of subvalvular structures.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are feasible in almost 95% of patients with degenerative MR despite the presence of complex lesions (3). The operative mortality and morbidity for isolated mitral valve repair is low, and early failures are uncommon in experienced hands (4)(5)(6)(7). While the repair for the prolapse of the posterior leaflet with valvular resection is usually possible, correction of anterior or bileaflet prolapse may also be feasible with more complex repair procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Werden die unbekannten Todesursachen hälftig den kardio-vaskulären und nicht den kardialen zugeordnet, so steigt das Risiko nach MKR an einer kardio-vaskulären Ursache zu sterben auf knapp 50%. Dieser Wert liegt etwas über demjenigen von 40%, den das Bundesamt für Statistik für die Gesamtbevöl-kerung während der letzten 10 Jahre beobachtet hat [6] [14][15][16][17].…”
Section: Abbildungunclassified